Parallel lines - St. Aubyn, Edward, 1960- (Alfred A. Knopf, 2025)
The fates of Sebastian and his therapist Martin, as well as radio producer Olivia, best friend Lucy, and husband Francis, are improbably yet inextricably linked in a novel about extinction and survival, inheritance and loss.